(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Cement being the binder in concrete production, is an extensive industrial commodity, the production of which leads to the emission of a vast amount of carbon dioxide which causes greenhouse gas emission and global warming. There is need for alternative materials that are environmentally friendly, economical and accessible. The research investigates the strength properties of concrete produced with volcanic ash and metakaolin as a partial cement replacement. Cement was partially replaced at 5%, 10%, 15%, 20%, 25% and 30%. Volcanic-metakaolin Fresh and hardened strength tests on mortar and concrete were carried out by adding 0–30% pozzolana, in which the water-to-binder ratio was 0.5 kept the same for all replacement levels. Density, compressive strength, flexural strength, and water absorption tests were carried out. Incorporation of volcanic ash and metakaolin reduces total voids in concretes. The result showed that VA-MTK has a pozzolanic effect on concrete properties by considering the strength activity index, higher compressive strength, higher flexural and splitting strength comparable to the control concrete 10% pozzolanic content. The maximum compressive strength at 28 days was the 10% VA/MTK as partial cement replacement, which achieved 28.5N/mm2 compared to the control, which achieved 28.2N/mm2. The flexural strengths at 10% achieved 5.22N/mm2, while the control concrete achieved 5.11 N/mm2. Considering the environmental and strength performance, a 15% cement replacement with metakaolin was convincing. Thus, the research shows that the use of VA/MTK as a partial replacement for cement in concrete, at a lower volume of replacement, will enhance the reduction of cement...